Rethinking social studies and citizenship in turkey. An overview to the 6th international symposium on social studies education - (:unkn) unknown (Bielefeld University, 2017)
[No abstract available]
Keywords: Citizenship education; International symposium on social studies education; Social studies education; Turkey